Molecular ageing of alpha- and beta-synucleins: protein damage and repair mechanisms - Vigneswara, Vasanthy; Cass, Simon; Wayne, Declan; Bolt, Edward L.; Ray, David E.; Carter, Wayne (Public Library of Science, 2013)
Abnormal α-synuclein aggregates are hallmarks of a number of neurodegenerative diseases. Alpha synuclein and β-synucleins are susceptible to post-translational modification as isoaspartate protein damage, which is regulated in vivo by the action of the repair enzyme protein L-isoaspartyl O-methyltransferase (PIMT). We aged in vitro native α-synuclein, the α-synuclein familial mutants A30P and A53T that give rise to Parkinsonian phenotypes, and β-synuclein, at physiological pH and temperature for a time course of up to 20 days. Resolution of native α-synuclein and β-synuclein by two dimensional techniques showed the accumulation of a number of post-translationally modified forms of both proteins. The levels of isoaspartate formed over the 20 day time course were quantified by exogenous methylation with PIMT using S-Adenosyl-L-[3H-methyl]methionine as a methyl donor, and liquid scintillation counting of liberated 3H-methanol. All α-synuclein proteins accumulated isoaspartate at ~1% of molecules/day, ~20 times faster than for β-synuclein. This disparity between rates of isoaspartate was confirmed by exogenous methylation of synucleins by PIMT, protein resolution by one-dimensional denaturing gel electrophoresis, and visualisation of 3H-methyl esters by autoradiography. Protein silver staining and autoradiography also revealed that α-synucleins accumulated stable oligomers that were resistant to denaturing conditions, and which also contained isoaspartate. Co-incubation of approximately equimolar β-synuclein with α-synuclein resulted in a significant reduction of isoaspartate formed in all α-synucleins after 20 days of ageing. Co-incubated α- and β-synucleins, or α, or β synucleins alone, were resolved by non-denaturing size exclusion chromatography and all formed oligomers of ~57.5 kDa; consistent with tetramerization. Direct association of α-synuclein with β-synuclein in column fractions or from in vitro ageing co-incubations was demonstrated by their co-immunoprecipitation. These results provide an insight into the molecular differences between α- and β-synucleins during ageing, and highlight the susceptibility of α-synuclein to protein damage, and the potential protective role of β-synuclein.